Nutritional effects on odour emissions in broiler production. Issue 2 (1st June 2017) - Sharma, N.K.; Choct, M.; Wu, S.; Swick, R.A.
Abstract : Odour emissions are a normal part of broiler production but they potentially threaten the sustainable development of the broiler industry. There are currently no effective methods to reduce odour emissions that are practical or affordable for use in commercial farms. Diets can be formulated to more closely meet the bird's nutritional requirements to avoid overfeeding and to reduce the excretion of undigested components. This will decrease the amount of substrates that the microbes metabolise to odorous compounds. Diet can affect gut microflora, faecal microflora, litter moisture content, pH and water activity, all of which may affect the emission of odorants. This review details the role of diets on odour emission from broiler production. In the first part of this review, key odorants from broiler production, their origin, and measurement techniques have been discussed. This is followed by the role of feed ingredients, enzymes, feed additives, minerals, dietary protein levels, necrotic enteritis and litter conditions on odour emissions. It has been reported that nutritional strategies such as partial replacement of soybean meal with meat meal in the diet, use of a low sulphur diet, low protein diet, Bacillus subtilis based probiotic and saponin may reduce emissions. Additionally, drying the litter results in lower emission of odorants including the ones that contain sulphur and prevention of necrotic enteritis and wet litter condition may also reduce odour emission from broiler production.